2020
DOI: 10.1002/app.49599
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin, an efficient natural stabilizer for both polyethylene and polypropylene

Abstract: Puerarin, a natural compound, was used as multifunctional protector for polyethylene (PE) and polypropylene (PP). Firstly, puerarin and tetrakis(2,4‐di‐tert‐butylphenol)[1,1‐biphenyl]‐4,4′‐diylbisphosphite (PEPQ) could protect PE and PP against thermos‐oxidative degradation: after modification, the oxidation induction time (OIT) of increased ca. 4,160% (PE‐P1200‐P sample) and 130% (PP‐P1200‐P sample); the carbonyl index (CI) obtained through accelerated aging decreased ca. 58% (PE‐P1200‐P sample). Secondly, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…2 Then, various fillers and reinforcements, such as graphene oxide, mesophase pitchbased carbon fiber, and carbon nanotubes, were explored to enhance the mechanical, thermal, and electrical properties of copper-clad laminates. 3 In parallel, studies focused on the development of flame-retardant formulations and conductive properties of copper-clad laminates. Flame retardant coatings based on phosphorus/boron-containing epoxy were developed, showcasing improved flame retardancy.…”
Section: Introductionmentioning
confidence: 99%
“…2 Then, various fillers and reinforcements, such as graphene oxide, mesophase pitchbased carbon fiber, and carbon nanotubes, were explored to enhance the mechanical, thermal, and electrical properties of copper-clad laminates. 3 In parallel, studies focused on the development of flame-retardant formulations and conductive properties of copper-clad laminates. Flame retardant coatings based on phosphorus/boron-containing epoxy were developed, showcasing improved flame retardancy.…”
Section: Introductionmentioning
confidence: 99%
“…29 Moreover, mango seed wax, an agro-industrial waste from the mango fruit processing industry has been used as an antioxidant plasticizer for PLA packaging applications, which increases the oxidation induction time of the PLA by 23%. 30 In our previous works, bamboo leaves, 31 punica granatum peel, 32 green tea waste, 33 pine needle, 34 puerarin, 35 and forsythia suspense 36 were used as natural antioxidants, which effectively improved the thermal oxidation stability of polyethylene and polypropylene. Among them, puerarin, and forsythia suspense are common traditional Chinese herbal medicines and are a potential source of antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…36 In addition, it is reported that the biological nanocomposites of cumin essential oil/PBAT/organic clay were prepared by solvent casting approach, which exhibited improved UV barrier performance, antibacterial and antioxidant activity. 37 In our previous works, some natural substances have shown strong antioxidant activity, such as bamboo leaves, 38 punica granatum peel, 39 pine needle, 40 puerarin, 41 forsythia suspense, 42 and scutellaria baicalensis. 43 The extracts of these substances have been used to modify polyethylene, polypropylene, and polylactic acid, all of which have obtained polymer composites with excellent thermal oxygen stability.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous works, some natural substances have shown strong antioxidant activity, such as bamboo leaves, 38 punica granatum peel, 39 pine needle, 40 puerarin, 41 forsythia suspense, 42 and scutellaria baicalensis 43 . The extracts of these substances have been used to modify polyethylene, polypropylene, and polylactic acid, all of which have obtained polymer composites with excellent thermal oxygen stability.…”
Section: Introductionmentioning
confidence: 99%